2000
DOI: 10.2466/pms.2000.90.2.691
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Emotional State and Performance during International Field Hockey Matches

Abstract: The present study examined the relationship between the emotions experienced by 15 international hockey players, both immediately before and during competition, and their performance levels. Data were collected on the players' emotional states using a revised version of the Feelings Scale of Butler, which was completed retrospectively after the match was played. Players reported more annoyance and less tension during the match than before. A logistic regression correctly classified 70.2% of players from the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Researchers have demonstrated that a wide range of emotions are associated with changes in performance levels (e.g., Burton, 1988;Gould, Petlichkoff, Simons, & Vevera, 1987;Hanin, 2000;Hanin & Syrjä, 1995a;Hanin & Syrjä, 1995b;Jones, Mace, & Williams, 2000). Recently, Botterill and Brown (2002), Hanin (2000), Lazarus (2000b), and Vallerand and Blanchard (2000) have all outlined the mechanisms by which emotions may influence performance.…”
Section: How Emotions Impact Sport Performancementioning
confidence: 99%
“…Researchers have demonstrated that a wide range of emotions are associated with changes in performance levels (e.g., Burton, 1988;Gould, Petlichkoff, Simons, & Vevera, 1987;Hanin, 2000;Hanin & Syrjä, 1995a;Hanin & Syrjä, 1995b;Jones, Mace, & Williams, 2000). Recently, Botterill and Brown (2002), Hanin (2000), Lazarus (2000b), and Vallerand and Blanchard (2000) have all outlined the mechanisms by which emotions may influence performance.…”
Section: How Emotions Impact Sport Performancementioning
confidence: 99%
“…In most cases, the study of the relationship between emotion andperformance has been oriented toward an analysis of the influence of emotion, particularly precompetitionemotion, on performance. To our knowledge, few studies have described theemotions actually experienced during competition and the way they influence athletic activity(e.g., Jones, Mace, & Williams, 2000;Robazza, Bortoli, &Nougier, 2000;Ruiz &Hanin, 2004;Syrja¨ ,Hanin, &Tarvonen, 1995). Several authors (e.g., Cerin, Szabo, Hunt, & William, 2000;D'Urso, Petrosso, &Robazza, 2002;Hanin, 2000) have nevertheless insisted on the need forstudies on the emotions actually experienced during competitions since emotions are modified byactions and the events that one encounters while competing.…”
Section: Introductionmentioning
confidence: 99%
“…Non-midfielders and forwards were more nervous than defenders and mid fielders. The latter, in turn, were less confident than de fenders [134].…”
Section: Psychologymentioning
confidence: 91%